2016
DOI: 10.1016/j.jhin.2015.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Ozonated water is inferior to propanol-based hand rubs for disinfecting hands

Abstract: Ozone is a strong oxidizing biocide that has broad-spectrum antimicrobial properties. The aim of the study was to compare the efficacy of ozone to a propanol-based hand rub for hand disinfection. Twenty subjects were enrolled in an in-vivo cross-over trial (prEN 12791). Subjects treated their hands with the reference procedure (propan-1-ol 60%) or with ozone (4 ppm). Post-wash bacterial counts were determined from one hand (immediate effect), and from the other hand that had been gloved for 3h (delayed effect)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…Ozonated water may show a limited effect on microorganisms depending on the conditions, but highconcentration ozonated water (≥10 mg/L) has enough of an effect even in the presence of inhibitory materials such as proteins (Hirai et al 2019). Although mediumconcentration (4 mg/L) ozonated water may be equivalent or slightly inferior to propanol (60%)-based hand rubs for disinfecting hands (Appelgrein et al 2016), one of the advantages of ozonated water is that it causes marginal or no skin damage when disinfecting hands (Breidablik et al 2019(Breidablik et al , 2020. Considering these issues, the fact that higher concentrations of ozonated water show stronger inactivating effects on SARS-CoV-2 may be a useful finding when using ozone-based hand disinfectants to prevent fomite infection.…”
Section: Discussionmentioning
confidence: 99%
“…Ozonated water may show a limited effect on microorganisms depending on the conditions, but highconcentration ozonated water (≥10 mg/L) has enough of an effect even in the presence of inhibitory materials such as proteins (Hirai et al 2019). Although mediumconcentration (4 mg/L) ozonated water may be equivalent or slightly inferior to propanol (60%)-based hand rubs for disinfecting hands (Appelgrein et al 2016), one of the advantages of ozonated water is that it causes marginal or no skin damage when disinfecting hands (Breidablik et al 2019(Breidablik et al , 2020. Considering these issues, the fact that higher concentrations of ozonated water show stronger inactivating effects on SARS-CoV-2 may be a useful finding when using ozone-based hand disinfectants to prevent fomite infection.…”
Section: Discussionmentioning
confidence: 99%
“…Ozone water may show a limited effect on microorganisms depending on the conditions, but high-concentration ozone water (≥10 mg/L) has enough of an effect even in the presence of inhibitory materials such as proteins [16]. Although medium-concentration (4 mg/L) ozone water may be equivalent or slightly inferior to propanol (60%)-based hand rubs for disinfecting hands [23], one of the advantages of ozone water is that it causes marginal or no skin damage when disinfecting hands [17, 18]. Considering these issues, the fact that higher concentrations of ozone water show stronger inactivating effects on SARS-CoV-2 may be a useful finding when using ozone-based hand disinfectants to prevent fomite infection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown ozonated water to irritate skin less than traditional sanitizers (Breidablik et al 2019;Kashiwazaki et al 2020), increasing the interest in ozonated water as an alternative handwashing treatment. However, current knowledge is based entirely on the reduction of laboratory-propagated bacterial species inoculated onto hands (Appelgrein et al 2016;Breidablik et al 2019;Nakamura et al 2018); there are currently no studies evaluating inactivation of viruses.…”
Section: Handwashingmentioning
confidence: 99%